Restructuring Interlinked With Employer and Corporate Branding Amidst COVID-19: Embodying Crowdsourcing - Sabir, Raja Irfan; Nazri, Mohammad; Majid, Muhammad Bilal; Mahmood, Hamid; Abbas, Khurram; Bano, Sobia (Frontiers in Psychology, 2022)
This conceptual research defines how the Covid-19 pandemic appears to be utterly uncertain over the world. The core point of this research is to draw a new conceptual framework depicting the ramifications of restructuring processes carried out by management for their organizations amidst the Covid-19 pandemic; on an Institute's reputation as an employer brand. It also investigates the impact of perceived restructuring on a corporate brand promise made by the university or institute from the viewpoints of other key stakeholders and potential job seekers. The philosophy of Positivism and the Deductive approach have been used for this research. A Self-Administered Questionnaire Survey was conducted to collect data to evaluate the cause and effect relationships of the constructs for this study in the education industry using a cross-sectional time horizon. For data analysis, the SEM technique has been used. This study shows that restructuring and employer branding has a negative and insignificant effect upon each other. The second direct hypothesis of the study that measures the effect of restructuring on corporate branding has been accepted. A corporate brand is a kind of a hub of all and it considers how an institute treats and deals with all of its stakeholders. It is different from employer brand as employees’ perceptions were the main focus. So, according to the results restructuring didn’t cause massive damage to the overall outlook of the institute. Furthermore, the mediation analysis depicted interesting results as well. For this purpose maximum likelihood method by bootstrapping was adopted to test the indirect hypotheses of the study. Firstly, the study analyzed mediation among crowdsourcing, restructuring, and employer branding which was fully accepted as results showed full mediation. Secondly, the study analyzed mediation among crowdsourcing, restructuring and corporate branding which was partially accepted as results showed partial mediation between these constructs. The study results will help management to understand that how they can improve their image in minds of employees and the general public by using the wisdom of the crowd through many means amid the covid-19 pandemic or other pandemics.